PROTEINURIA AND ACUTE PHYSICAL EFFORT - Radu M.D; Șchiopu S.; Tuță L.A; Chirică R. (ALTIUS ACADEMY Foundation - Faculty of Physical Education and Sports, 2015)
It is well known that intense exercise leads to increased urinary excretion of protein, a phenomenon encountered both in experimental models in laboratory animals and in amateur and professional athletes, where proteinuria mechanism is still unclear. Proteinuria is an important marker of physiological integrity of the excretory system. Proteinuria after exercise, induced the effect of physical exercise on renal function. During physical exertion blood flow is directed mainly towards skeletal muscles that are in business, to the detriment of many organs that are subjected to transient ischemia. Ischemic reperfusion is an important source of activation and generation of oxygen free radicals in organs involved in supporting passive exercise. The effects of biochemical or functional neurons induced oxygen free radicals play an important role in urinary protein excretion. Therefore, exercise is an inducer of oxidative stress phenomenon not only in skeletal muscle in operation. Experimental study quantify the biochemical adaptation of functional kidney in one workout. Experimental results suggest that functional alterations of neuronal membranes, due to oxygen free radicals actions are a cause of proteinuria after exercise in laboratory animals.